Industrial heritage and urban renewal: a quantitative study and optimization strategies for Chengdu East Suburb Memory - Xia, Jun; Wang, ShaoQing; Cheng, Ai (Frontiers in Environmental Science, 2025)
IntroductionThe acceleration of urbanization and industrial restructuring in recent years has positioned the regeneration of industrial heritage as a critical issue in urban renewal and sustainable development. However, existing research predominantly focuses on design and conservation, lacking systematic quantitative analysis of user satisfaction, which limits holistic optimization of regeneration outcomes.MethodsThis study employs a mixed-methods approach, integrating Structural Equation Modeling (SEM) and Importance-Performance Analysis (IPA) to quantitatively evaluate user satisfaction. A satisfaction evaluation system was constructed across six dimensions—cultural identity, environmental sustainability, social impact, technology application, spatial layout, and economic value—and empirically validated through questionnaire surveys and statistical analysis.ResultsThe SEM analysis revealed that social impact exerts the strongest influence on user satisfaction, emphasizing the role of community interaction and public participation. Economic value and environmental sustainability ranked second, highlighting the significance of economic benefits and ecological improvements. Cultural identity and spatial layout showed weaker effects, suggesting insufficient integration of cultural and technological elements. IPA further identified key areas for improvement, such as intelligent management systems and transportation convenience.DiscussionThe findings underscore the necessity of prioritizing community engagement and economic-environmental synergies in industrial heritage regeneration. While cultural and spatial factors require deeper integration, technological innovations should be leveraged to enhance functional performance. These insights provide policymakers and urban planners with actionable strategies to balance social, economic, and cultural benefits, advancing sustainable urban development goals. The study bridges the gap between qualitative preservation and quantitative user-centric evaluation, offering a replicable framework for future heritage regeneration projects.